Opinion on the Working Environment and Problems Faced by the Women Workers in Hosiery Units at Tiruppur, Tamil Nadu - An Empirical Investigation - Saravanan, S. (Prabandhan: Indian Journal of Management, 2010)
Tiruppur is a textile town in Coimbatore District of Tamil Nadu and is popularly known as Banian City, Knit City and Dollar city. Tiruppur is the "Knitwear capital" of India. Tiruppur contributes to a huge amount of foreign exchange in India. It has spurred up the textile industry in India for the past three decades. Its economic boom boosts the morale of I ndian industrialists.